Decoding RAGE in diabetes: a pathogenic signaling hub modulated by decoy receptors in diabetic complications - Yupa Srithongchai; Ai Harashima; Seiichi Munesue; Kumi Kimura; Yu Oshima; Mariko Tanaka; Hiroya Takahashi; Pathitta Sakulsak; Chisato Uramoto; Nontaphat Leerach; Yasuhiko Yamamoto (Frontiers in Clinical Diabetes and Healthcare, 2026)
Diabetes is characterized by chronic hyperglycemia and dyslipidemia, which impose sustained metabolic stress and drive the development of diabetic complications. In this review, we position the axis between advanced glycation end-products (AGEs) and the receptor for AGEs (RAGE) as a central hub that couples metabolic stress to persistent cellular stress and inflammatory responses. Ligand engagement of full-length membrane-bound RAGE (mRAGE) enhances reactive oxygen species (ROS) generation and activates nuclear factor kappa B (NF-κB), establishing a self-amplifying feed-forward loop that promotes RAGE expression, inflammation and further AGE accumulation. RAGE exhibits marked structural heterogeneity: in addition to signaling-competent mRAGE, soluble decoy receptors—including soluble RAGE (sRAGE) produced by ectodomain shedding and endogenous secretory RAGE (esRAGE) generated by alternative splicing—sequester ligands and attenuate downstream signaling. Moreover, RAGE recognizes a broad ligand repertoire beyond AGEs, such as S100 proteins and high-mobility group box 1 (HMGB1), reinforcing its role as an integrator of metabolic and sterile inflammatory cues. Notably, RAGE also mediates physiological transport of oxytocin across the blood–brain barrier (BBB), a process implicated in oxytocin-dependent social behaviors, without activating canonical, pro-inflammatory RAGE signaling. Accordingly, therapeutic strategies should selectively suppress pathogenic, ligand-driven RAGE signaling and/or augment decoy RAGE activity while preserving RAGE-dependent oxytocin transport.